Pharmacist involvement in the patient care improves outcome in hypertension patients - Pranay Wal; Ankita Wal; Anil Bhandari; Ummeshwar Pandey; Awani K Rai (Wolters Kluwer Medknow Publications, 2013)
Objective: The main objective of this study was to assess the effects of pharmaceutical care interventions in patients with essential hypertension in Lakshmi Pat Singhania Institute of Cardiology, Kanpur, India. Methods: The study was carried out from July 2010 to August 2011. Pharmaceutical care was provided for 54 patients (intervention group) which was comprised of the patient education, the prescription assistance and the life style modifications and motivation for health. Then the clinical outcome as well as health related quality of life (HRQOL) were compared with the control group (48 patients) in which the pharmaceutical care was not provided. Furthermore, the effect of pharmaceutical care intervention on HRQOL was assessed using Short Form-36 (SF-36), a general health related quality of life questionnaire used to evaluate the QOL of patients. Blood pressure (BP) measurements and QOL survey was performed at baseline and at the follow-up session. Findings: The difference between blood pressure readings from the baseline to the second follow-up was significant for systolic [(P = 0.0001), 12.24 mmHg] and diastolic BP [(P = 0.001), 5.17 mmHg] in the intervention group. The questionnaire used to evaluate the QOL of patients also showed improvement in the mean score for intervention group. Conclusion: Results from our study showed that applying pharmaceutical care to hypertensive patients can help in the control of these patients' blood pressure, and consequently lower the risk that hypertension poses in cardiovascular disease. Successful implementation of pharmaceutical care has the potential to increase patients' satisfaction with their pharmacists' activities and may increase patients' expectations that pharmacists will work on their behalf to assist them with their healthcare needs.